How does nano-focus computed tomography impact the quantification of debris within the root canal system? - Clarissa Teles RODRIGUES; Reinhilde JACOBS; Mostafa EZELDEEN; Karla de Faria VASCONCELOS; Paul LAMBRECHTS; Mario TANOMARU FILHO; Jader Camilo PINTO; Marco Antonio Hungaro DUARTE (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The aim of this study was to compare the quantification of hard-tissue debris by using micro-computed tomography (micro-CT) and nano-focus computed tomography (nano-CT) after root canal instrumentation. Ten mandibular molars containing an isthmus in the mesial root were scanned in a SkyScan 1172 micro-CT device with a voxel size of 12.8 µm and in a NanoTom nano-CT device with 5.5 µm. The mesial root canals were irrigated with 5 mL of saline solution at the orifice level, instrumented with Reciproc R25 files and a second scanning was performed by micro-CT and nano-CT devices for post-instrumentation images. DataViewer software was used for registering the pre- and post-operative micro-CT and nano-CT images. The root canal and the debris were segmented for quantitative analysis of the volume of the canal and volume of debris using CTAn software. Statistical analysis was performed using the T test for comparison between volume of the canal after instrumentation and volume of debris in both image modalities. The level of significance was set at p < 0.05. Nano-CT images showed higher values of debris when compared with micro-CT (p < 0.05) after root canal instrumentation. No difference was observed between the volume of the root canal after instrumentation in the two imaging methods used (p > 0.05). Nano-CT technology can be recommended as a more precise method for quantitative analysis of hard-tissue debris. Moreover, in Endodontic research it is a promising method, as it is capable of providing higher spatial and contrast resolution, faster scanning and higher image quality.